2021
DOI: 10.1002/pc.26007
|View full text |Cite|
|
Sign up to set email alerts
|

Degradation analysis of epoxy resin composites reinforced with bioprotein: Effects of hydrolysis using papain and bromelain

Abstract: Degradation of epoxy‐based composites reinforced with fish scale particles was studied using two enzymes, papain, and bromelain. Mechanical, structural, thermal, and morphological properties of the composites were characterized. Results showed a significant deterioration of the properties after the degradation of the composites. Flexural strength of the composites was reduced by 38% and 13%, respectively, due to the presence of the enzymes. Crystalline temperature of the composites was significantly decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The continued action of the enzymes and cells eventually resulted in erosion marks. In a recent study by Faiza et al (2021), the surface of composites showed similar cracks and erosion after treatment with the plant-derived proteases papain and bromelain. At the same time, the AFM results showed that the surface of PP particles incubated with bacteria showed obvious depression (Figure S2b), which were not obserced in the control group (Figure S2a), consistent with the SEM results.…”
Section: Surface Topography Analysis Of Degraded Pp Particles By Sem ...mentioning
confidence: 81%
“…The continued action of the enzymes and cells eventually resulted in erosion marks. In a recent study by Faiza et al (2021), the surface of composites showed similar cracks and erosion after treatment with the plant-derived proteases papain and bromelain. At the same time, the AFM results showed that the surface of PP particles incubated with bacteria showed obvious depression (Figure S2b), which were not obserced in the control group (Figure S2a), consistent with the SEM results.…”
Section: Surface Topography Analysis Of Degraded Pp Particles By Sem ...mentioning
confidence: 81%
“…Bromelain is a plant protease obtained from the pineapple stem, broadly used in the food industry and able to catalyze the hydrolysis of proteins into amino acids 73 . Its capacity to promote collagen hydrolysis has been verified experimentally 74 , 75 . Similarly, papain is obtained from papaya and is a cysteine protease known for its specificity, commonly used in atraumatic dental procedures as a chemo-mechanical method to remove caries-affected substrate 73 .…”
Section: Discussionmentioning
confidence: 92%
“…Polymers have a wide range of applications for its excellent electrical, mechanical, thermal and optical properties. 99,100,101,102,103,104 CPs are able to utilize the entire material into the charging process while the only surfaces are involved in the charging process in case of other ordinary electrode materials. During the redox reaction in CPs, electrons from the electrolyte transport into and out of the polymeric chains.…”
Section: Capacitancementioning
confidence: 99%